PENGARUH DANA PERIMBANGAN DAN KEMANDIRIAN KEUANGAN DAERAH TERHADAP KESERASIAN ANGGARAN DAN KESEJAHTERAAN MASYARAKAT PADA KABUPATEN/KOTA DI PROVINSI BALI - swandewi, agung (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME 03. NO.07.TAHUN 2014, 2014)
Normal 0 false false false EN-US X-NONE X-NONE Since 2001, Indonesia's regional autonomy exercised simultaneously . The purpose of implementation of regional autonomy is to improve the well-being of society . This study aims to determine the effect of Balanced Funds and Regional Financial Survival for compatibility estimates and Welfare Society in Regency / City in the Province of Bali . Data obtained from secondary sources from the Central Statistical Agency and the Bureau of Finance Setda Bali Province . Further analysis of the data was analyzed by band represents the development of regression methods . The results showed that the fund balance the district 's financial independence and a positive influence on the compatibility of budget , the fund balance is not significant at the 5 percent significance level . Kemandiriaan financial district , fund balance , and the district 's financial compatibility is positive for the community. The fund balance of no significant indirectly to the welfare of society through compatibility estimates, while the district 's financial kemandiriaan significant indirect effect on the well-being of society through the compatibility of estimates. Keywords: fund balance , the district 's financial independence , compatibility estimates, the welfare of society
Keywords: balance fund, the financial independence, harmony budget, the public welfare